Headache and Stomach-Ache Co-occurrence Syndrome - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1995)
Psychosocial risk factors for headache and stomache-ache and their co-occurrence were investigated in a longitudinal study of Norwegian children aged 4-10 years at the Department of Health and Society, National Institute of Public Health, Oslo, Norway.